Addressing Planetary Health through the Blockchain—Hype or Hope? A Scoping Review - Rita Issa; Chloe Wood; Srivatsan Rajagopalan; Roman Chestnov; Heather Chesters; Geordan Shannon (Challenges, 2023)
Planetary health is an emergent transdisciplinary field, focused on understanding and addressing the interactions of climate change and human health, which offers interventional challenges given its complexity. While various articles have assessed the use of blockchain (web3) technologies in health, little consideration has been given to the potential use of web3 for addressing planetary health. A scoping review to explore the intersection of web3 and planetary health was conducted. Seven databases (Ovid Medline, Global Health, Web of Science, Scopus, Geobase, ACM Digital Library, and IEEE Xplore) were searched for peer-reviewed literature using key terms relating to planetary health and blockchain. Findings were reported narratively. A total of 3245 articles were identified and screened, with 23 articles included in the final review. The health focus of the articles included pandemics and disease outbreaks, the health of vulnerable groups, population health, health financing, research and medicines use, environmental health, and the negative impacts of blockchain mining on human health. All articles included the use of blockchain technology, with others additionally incorporating smart contracts, the Internet of Things, artificial intelligence and machine learning. The application of web3 to planetary health can be broadly categorised across data, financing, identity, medicines and devices, and research. Shared values that emerged include equity, decentralisation, transparency and trust, and managing complexity. Web3 has the potential to facilitate approaches towards planetary health, with the use of tools and applications that are underpinned by shared values. Further research, particularly primary research into blockchain for public goods and planetary health, will allow this hypothesis to be better tested.